Study of effect of temperature on behavior of alkali activated slag concrete. (2021) - Ray, Tanushree; Ranjan Mohanta, Nihar; Hitesh Kumar, Mavoori; Saikrishna macharyulu, Ippilli; Samantaray, Sandeep
Abstract: In this work, the effect of temperature on behaviour of AASC (Alkali Activated Slag Concrete) with that of Conventional concrete (CC) is made. For this a design mix of M20 grade has been made in accordance with IS 10262:2009. Preliminary investigations has been done for 18 mixes and the mix S-0.5–1-12 M is considered as the best, based on strength characteristics, in which AAS (Alkali Activated Slag) to GGBS (Ground Granulated Blast Furnace Slag) ratio is 0.5 with Na2 SiO3 solution (SSS: Sodium Silicate Solution) to NaOH solution (SHS: Sodium hydroxide Solution) ratio1.0 containing concentrated 12 M of NaOH solution. The alkaline solution has been prepared 24 h in advance to the casting process. The conventional method of mixing, compacting and moulding has been followed for the production of AASC. Total of 144 cubes of dimension 150x150x150 mm, 180 cylinders of dimension 150x300mm and 144 prisms of dimension 500x100x100mm were casted. The specimens are subjected to ambient curing for 7, 28, 56 and 91 days and then subjected to temperatures of 27 0, 100 0, 200 0, 300 0, 400 0 and 500 °C for a period of 1 h. From the above study it was found that various Mechanical Properties of AASC mix performing better than CC (Conventional Concrete) mix.